2011
DOI: 10.1186/1471-244x-11-55
|View full text |Cite
|
Sign up to set email alerts
|

The impact of study design and diagnostic approach in a large multi-centre ADHD study: Part 2: Dimensional measures of psychopathology and intelligence

Abstract: BackgroundThe International Multi-centre ADHD Genetics (IMAGE) project with 11 participating centres from 7 European countries and Israel has collected a large behavioural and genetic database for present and future research. Behavioural data were collected from 1068 probands with ADHD and 1446 unselected siblings. The aim was to describe and analyse questionnaire data and IQ measures from all probands and siblings. In particular, to investigate the influence of age, gender, family status (proband vs. sibling)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 35 publications
(52 reference statements)
0
43
1
Order By: Relevance
“…In comparison to teachers, parents have much better and more frequent opportunities to observe also emotional problems in their children so that there was a much better differentiation of the groups regarding behavioural domains other than ADHD by the parents in the present study. These findings differ from those by Müller et al [19,20 ], who found smaller informant effects in emotional problems.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In comparison to teachers, parents have much better and more frequent opportunities to observe also emotional problems in their children so that there was a much better differentiation of the groups regarding behavioural domains other than ADHD by the parents in the present study. These findings differ from those by Müller et al [19,20 ], who found smaller informant effects in emotional problems.…”
Section: Discussioncontrasting
confidence: 99%
“…This study found larger differences between probands and siblings at home than at school in most of the behavioural scores reflecting contrast effects in the parents [19,20].…”
Section: Introductionmentioning
confidence: 46%
See 2 more Smart Citations
“…Participants were selected from the Dutch follow-up phase of the International Multicenter ADHD Genetics (IMAGE) study [34][35][36] . ADHD diagnosis, ADHD severity, and presence of comorbid disorders were established using an algorithm based on both the Schedule for Affective Disorders and Schizophrenia for School-Age Children (K-SADS 37 ) and Conners' ADHD questionnaires for parents 38 …”
Section: Participantsmentioning
confidence: 99%